The Correlation Between Quality of Nurse Services and Hospital Services towards Satisfaction and Patient Comfort in Covid-19 Disease Recovery in Hospital - Emirensiana Anu Nono (STIKES Ngesti Waluyo, 2022)
The cases of Covid-19 which are increasing every day encouraging services in hospitals to be responsive, fast and precise in serving Covid-19 patients. Quality of service is needed to provide satisfaction to patients. The objective of this research is to know the correlation between patient satisfaction, restoring trust and nursing care and quality of services in St Elisabeth Hospital Semarang. The design of this research is a correlational research. The number of respondents were 77 people, who had experienced Covid-19 illness in Rs. St. Elisabeth Hospital and agreed to fill in the researcher's questions electronically in the researcher's Google Drive. The analysis shows that there is a correlation between the Nursing Care and Patient Satisfaction, with the correlation coefficient is 0.749. This coefficient is in the high category because it is above 0.7, and the significance value of 0.00 which is below the Cut of value 0.05. Similarly, there is a significant correlation as well in variable Quality of services and Restoring Trust Patients. This analysis states that the hypothesis is proven, meaning that the better nursing care and quality of nursing services in a hospital are given, the better patient satisfaction is, and restoring patient trust.